Implementasi Pengurangan Risiko Banjir di Jakarta - Amiruddin, Muhammad; Herlina Juni Risma Saragih; Sovian Aritonang; Pujo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
Jakarta faces a major risk of flooding. Therefore, a strategy is needed for massive disaster risk reduction. This study aims to analyze the implementation of flood risk reduction in Jakarta. The research method uses a descriptive qualitative approach with data collection through interviews, observations, and secondary data. The existing condition of the flood risk reduction system in Jakarta is built by strengthening early warnings that are developed based on the analysis of information collected from various parties. There are at least six ways used by BPBD to build a flood risk reduction system in Jakarta, namely: (1) the use of social media disseminated through the network of Regional Apparatus Organizations (OPD) and the community, (2) DWS, AWLR and AWS technology (3) SMS blasting system in collaboration with the Ministry of Communication and Information Technology (Kominfo) and using the Base Transceiver Station (BTS) network in flood-prone areas, (4) the use of volunteer radio networks, (5) the use of Simba and (6) Flood Monitoring System. Each of these methods has an important role in disseminating early warning information and helping communities to act immediately in the face of flood threats. These methods have reflected efforts to build preparedness in line with the Sendai Framework for Disaster Risk Reduction 2015-2030. The main focus of implementing these tools as instruments for data collection, risk information management, and access to location-based information as the basis for disaster risk reduction efforts.